EXAMINING THE RELATIONSHIP BETWEEN POSITIVE AURA, INTERPERSONAL EFFECTIVENESS AND GENERATION GAP - Priyal, Vaidehi; N, Ramkumar (Journal of Contemporary Research in Management (JCRM), 2013)
Globalization is the cause for rapid increase in generation gap. Due to generation gap there is increase in conflicts between younger and older in workplace and family. To overcome generation gap, the most traditional method of increasing positive aura or energy is followed, which increases interpersonal effectiveness. Thus, the research study is to identify how to increase the interpersonal effectiveness in order to overcome generation gap using aura as a tool.Â Therefore the three research variables are, interpersonal effectiveness, generation gap and aura. This is a literature-based paper to examine the relationship among the variables and arrive at the theoretical framework for the research. For this purpose, about 80 literatures were collected and classified under three research variables: interpersonal effectiveness (IE), generation gap (GG) and aura. The literatures collected under interpersonal effectiveness focuses on identifying factors effecting interpersonal effectiveness, concept and constituents of IE, measures involved, and benefits of IE. The literatures collected under generation gap focuses on concept of GG and its measures. Similarly, literatures collected under aura focuses on what is aura and, its measures and application. Based on the review, it is observed that Interpersonal effectiveness is relatively proportional to productivity. So, for increase in productivity and organisational growth, there must be increased interpersonal effectiveness. As generation gap is due to deficiency in interpersonal understanding between young and old, which is believed that would be overcome by effective interpersonal effectiveness. Also, since the aura of the person is strongly associated with interpersonal attraction and communication, aura has been considered as a tool, for bridging generation gap by increasing interpersonal effectiveness.